In-depth morphological evaluation of tooth anatomic lengths with root canal configurations using cone beam computed tomography in North American population - Varun KULKARNI; Onurcem DURUEL; Emel Tuğba ATAMAN-DURUEL; Melek Didem TÖZÜM; Salvador NARES; Tolga Fikret TÖZÜM (University of São Paulo, 2020)
Abstract Objective This study aimed to assess the association between tooth size and root canal morphology by using CBCT analysis. Methodology In this retrospective study, tooth anatomic lengths (crown and root lengths, buccolingual and mesiodistal dimensions) of 384 patients were assessed and correlated with Vertucci's root canal morphology classification. Data was analyzed for gender-related differences using the independent sample t-test, ANOVA, and the Pearson's correlation for a possible relation between anatomic lengths and canal morphology. Results The maxillary first and second premolars showed a greater predilection for Type IV and II variants, respectively, while the mandibular first premolar showed a greater predilection for Type II canal system. The root canal system of the mandibular second premolar showed maximal diversity (47% Type I, 30% Type II, and 20% Type III). The dimensions were greater in men regardless of tooth type. The most significant relation (p<0.05) between the anatomic size and canal morphology was observed in the maxillary first premolars, followed by the mandibular canines (buccolingual dimension) and the lower second premolars (crown length). Negative correlations existed between the crown length and the patient's age for the anterior teeth and mandibular second premolar (r=−0.2, p<0.01). Conclusions The most common canal formation for anterior teeth was the Type I. The anatomic lengths had the strongest influence on the canal configuration of the maxillary first premolar, with Type IV being the most common root canal system. The mandibular second premolars showed maximal diversity in the canal classification terms and had a significant correlation with their crown lengths. Clinical Relevance The complex relationship between the canal morphology and anatomic tooth sizes need meticulous awareness and recognition during endodontic procedures, in conjunction with the demographic variabilities.